DESIGN AND IMPLEMENTATION OF A REMOTELY SURFACE VEHICLE (RSV EMAS) POWERED BY RENEWABLE ENERGY FOR AUTOMATED WATER QUALITY MONITORING - Sutrisno, Imam; Tibyani , Tibyani; Santosa, Ari Wibawa Budi; Subekti, Joko; Ardiansyah, Ardiansyah; Asmara, I Putu Sindhu; Pramanta, Dinda; Sutanto, Heri; Ahda Tanjung, Ihsan (Journal of Applied Engineering Science, 2025)
This paper presents the design, implementation, and field evaluation of RSV Emas, a compact, solar-powered, remotely operated surface vehicle (RSV) developed for autonomous water quality monitoring. The system introduces a novel integration of three key technologies: renewable energy harvesting for extended mission endurance, a fuzzy-PID hybrid control algorithm for adaptive navigation, and embedded piezoelectric actuators for real-time stabilization in dynamic aquatic conditions. RSV Emas is equipped with a multi-sensor suite capable of measuring temperature, pH, turbidity, and total dissolved solids, with data transmitted wirelessly to a remote dashboard. Field experiments in a controlled freshwater pond demonstrate that the vehicle can operate autonomously for over six hours under moderate sunlight, maintain stable trajectory with less than 0.5 m path deviation, and reduce tilt oscillations by up to 38% through smart material-based stabilization. These results confirm that RSV Emas offers a cost-effective, energy-efficient, and scalable platform for real-time water quality assessment, with potential applicability in environmental management and early pollution detection.
Keywords: autonomous surface vehicle, water quality monitoring, fuzzy-PID control, piezoelectric stabilization, solar-powered robotics